The Role of Extracorporeal Septorhinoplasty in Severely Deviated Noses: A Prospective Cross-Sectional Study - Mahato, Nain Bahadur; Piya, Sama; Pokharel, Pujan; Maharjan, Anil; Pradhan, Rosi (Nepal Journal of Medical Sciences, 2026)
Introduction: Patients with gross septal deviations often present with both aesthetic and functional problems, demanding precise preoperative evaluation and accurate surgical planning. Managing such gross septal deviations often present technical surgical challenges. Extracorporeal septorhinoplasty (ECS) is a reliable solution for treating severely deviated noses. This study aims to assess the functional and aesthetic outcomes of ECS in patients with markedly deviated noses. Methods: This prospective cross-sectional study, conducted at Kathmandu Medical College between February 2023 and April 2025, evaluated patients with severe nasal deviation treated using the ECS technique. Nasal obstruction was assessed pre- and postoperatively using a Visual Analog Scale (VAS), while anthropometric parameters such as nasofrontal, nasolabial, and external deviation angles were analyzed from standardized photographs taken six months after septorhinoplasty. Results: Among 68 patients (43 males, 25 females; aged 18–48 years) who underwent extracorporeal septoplasty, the mean operative time was 115 minutes. Postoperatively, all patients achieved a near-straight septum with significant improvement in nasal obstruction (VAS 8.41 ± 1.05 pre-op to 1.76 ± 0.99 at 6 months, p < 0.001). Marked aesthetic enhancement was also observed, with statistically significant improvements in the nasofrontal, nasolabial, and external deviation angles. Conclusions: Extracorporeal Septorhinoplasty offers a definitive solution for gross septal deviations, delivering durable structural correction, improved function, and high patient satisfaction. Continuous refinements and modifications in technique have solidified its role as a reliable approach in reconstructive nasal surgery.